Pensamento reflexivo e formação democrática em John Dewey - Schwengber, Ivan Luís (2023)
The thesis seeks to reconstruct the nexus between education and democracy, having as its guiding thread the formation of reflective thought in John Dewey. This is a bibliographical investigation, of a hermeneutic nature, focusing on the texts of the aforementioned author, taking as its main reference the work How We Think - How reflective thinking relates to the educational process: a re-exposition. The thesis was born and constituted at a sui generis moment in the history of democratic institutions on the international scene. Currently, public education, with its schools and teachers, is under attack from various sides by economic organizations and certain ideological, political and religious groups. Considering this context, the present research constituted, using John Dewey's thought, a form of formative and intellectual confrontation to resist reflexively through daytime activity from the classroom and teaching activity. The objective of the thesis is to reconstruct reflective thinking, as a form of democratic life, capable of linking it to the exercise of teaching and democratic cooperation. In the first chapter, the study problematizes the concept of reflective thinking, sticking to reasonable belief and guaranteed assertion. The second chapter investigates the formative aspect of reflective thought, focusing especially on the dispositions of the acting subject, on the formative and constitutive aspect of the category of experience, as well as on the phases proposed by Dewey of reflective thought itself. Such aspects constitute the formative core that supports the importance of experience to act intelligently. The third chapter deals with the educational aspect of reflective thinking as meaningful problem solving. Consider it in light of the theory of curiosity and the three fundamental aspects of attributing meanings, especially when considering concepts as meanings constituted by scientific research and the cooperative community. These are presented as decisive for the notion of democracy as a way of life in the educational space, as well as in broader democratic public spaces. Finally, the fourth and final chapter brings, in an updated way, to the classroom context, the implications of the formation of reflective thinking, conceiving it as an intellectual disposition for pedagogical action in an environment altered by information and communication technologies. The thesis concludes that the development of reflective thinking is a condition for the formation of autonomous subjects capable of cooperation and democratic interaction, constituting, at the same time, an indispensable reference for the reconstruction of democracy with each new generation.